Profesionalisme Pendidik PAUD Melalui Pendampingan Reflektif Dampak Terhadap Kualitas Interaksi Anak Usia Dini - Ratu Linda Martina Andryani; Sofia Hartati; Nurbiana Dhieni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Early Childhood Education (ECE) serves as a crucial foundation in developing quality human resources, with the 0–6 year age range constituting a golden period of brain development. However, the reality in Indonesia reveals that the quality of ECE teachers remains suboptimal, with approximately 52% yet to meet minimum academic qualifications. This study aims to explore the relationship between reflective mentoring programs and the enhancement of ECE teacher professionalism, as well as its impact on the quality of early childhood interactions. Employing a qualitative approach through systematic literature review, data were gathered from empirical journals, books, and national and international research reports published within the last 5 years, and analyzed using content analysis and thematic synthesis. The findings indicate that reflective mentoring implemented through coaching, mentoring, and structured peer observation significantly enhances teachers' pedagogical competence, self-reflective capacity, and emotional responsiveness. This improvement in professionalism, in turn, demonstrably affects the quality of teacher-child interactions, characterized by greater warmth, increased child engagement, and consistent emotional support. Indonesia's Teacher Professional Education Program (PPG) is identified as having substantial institutional potential as a vehicle for reflective mentoring, although its implementation still requires strengthening to be more contextual and sustainable.